1988
DOI: 10.1111/j.1365-2125.1988.tb03295.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resins and activated charcoal on the absorption of digoxin, carbamazepine and frusemide.

Abstract: 1. The interference of resins and activated charcoal with the absorption of digoxin, carbamazepine and frusemide was studied. 2. In a cross‐over study consisting of four phases, single doses of colestipol hydrochloride (10 g), cholestyramine (8 g), activated charcoal (8 g) or water only were given to six healthy volunteers immediately after the simultaneous ingestion of digoxin (0.25 mg), carbamazepine (400 mg) and frusemide (40 mg). Plasma and urine concentrations of the test drugs and the urine volumes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…A small dose of charcoal (8g) completely prevented (99.5%) the absorption ofa therapeutic dose (40mg) of frusemide (Neuvonen et al 1987). A small dose of charcoal (8g) completely prevented (99.5%) the absorption ofa therapeutic dose (40mg) of frusemide (Neuvonen et al 1987).…”
Section: Diureticsmentioning
confidence: 99%
“…A small dose of charcoal (8g) completely prevented (99.5%) the absorption ofa therapeutic dose (40mg) of frusemide (Neuvonen et al 1987). A small dose of charcoal (8g) completely prevented (99.5%) the absorption ofa therapeutic dose (40mg) of frusemide (Neuvonen et al 1987).…”
Section: Diureticsmentioning
confidence: 99%
“…In the publication by Lapatto-Reiniluoto, the authors reported a reduction of absorption of carbamazepine (measured as the AUC 0-24 ) by activated charcoal of 62% [31]. In another publication, the absorption of 400 mg oral carbamazepine was decreased greatly (90%) by activated charcoal [32].…”
Section: Discussionmentioning
confidence: 99%
“…Colestipol can affect the bioavailability of gemfibrozil, thiazide diuretics, propranolol, furosemide, tetracycline, and penicillin G [13]. Absorption of digoxin is not affected by colestipol [166]. Colesevelam did not decrease the absorption of digoxin, fenofibrate, lovastatin, warfarin, digoxin, metoprolol, quinidine and valproic [82,167].…”
Section: Adverse Effects and Drug Interactionsmentioning
confidence: 99%